Stakeholder Perceptions and the Mediated Effectiveness of Bilingual Education in Indonesian International Schools - Harmita Sari; Dedi Aco; Andi Syukri Samsuri; Samsinar Samsinar; Andi Nurhayati (AL-ISHLAH: Jurnal Pendidikan, 2025)
Bilingual education programs are increasingly implemented in Indonesian international schools; however, their effectiveness in improving learning outcomes remains contested. Prior studies often emphasize program design while overlooking the complex roles of curriculum practices and stakeholder involvement. This study investigates how bilingual education programs influence learning effectiveness through mediating factors from the perspectives of key stakeholders. A quantitative cross-sectional survey design was employed involving 523 participants (teachers, parents, and students) from Indonesian international schools implementing Immersion Program (IMM), Developmental Bilingual Education (DBE), and Two-Way Immersion (TWI) models. Data were collected through an online questionnaire and analyzed using Structural Equation Modeling (SEM) to examine direct and mediated relationships among bilingual programs, curriculum and teaching, stakeholder engagement, and learning effectiveness. The findings reveal that bilingual education programs do not have a significant direct effect on learning effectiveness. However, they significantly influence curriculum and teaching practices as well as stakeholder engagement. Both curriculum–teaching adaptation and stakeholder experiences demonstrated significant positive effects on bilingual learning effectiveness, with stakeholder engagement emerging as the strongest mediator. These results indicate that the effectiveness of bilingual education is contingent upon mediating processes rather than program implementation alone. The findings support complexity theory, emphasizing the dynamic interaction between curriculum design, pedagogical practices, and stakeholder involvement. This study highlights the necessity of human-centered and context-sensitive approaches in designing and implementing bilingual education programs to enhance learning outcomes in Indonesian international schools.